Castles and catastrophes - "Asquith, Ros" (piccadilly press London, 2006)
12-year-old Cordelia Arbuthnot longs to be a famous writer, but not like her aunt. Everyone loves her aunt's books, but Cordelia is determined to write something far more interesting and complex
Keywords: Children's stories Fiction